Gender atypical behavior in chinese school-aged children: Its prevalence and relation to sex, age, and only child status - Yu, L.; Winter, Sam (Common Ground Publishing LLC, 2011)
This study had three purposes: (a) to compare the prevalence of boys' and girls' gender-atypical behaviors (GABs) in a sample of Chinese school-aged children, (b) to examine the developmental pattern of GABs in Chinese boys and girls over the age range in question (6-12 years), and (c) to test the effects of being an only child on children's GAB expression. Parents of 486 boys and 417 girls completed a Child Play Behavior and Activity Questionnaire (CPBAQ) in regard to their own children, and a demographic information sheet. The frequency distribution for each gender-related behavior was calculated. The associations between sex, age, and only-child status, and CPBAQ scale scores were examined. Although most GABs (by their very nature) were exhibited infrequently in Chinese children, it was found that girls displayed GABs more frequently than boys did. The prevalence of GABs rose for girls as they grew older, but fell slightly for boys. The expressions of GABs in only children did not differ from that in children with siblings. Possible effects of Chinese culture (including the current only-child policy) on children's GABs are discussed. Copyright © The Society for the Scientific Study of Sexuality.